POSSIBILITIES OF ORGAN-PRESERVING TREATMENT OF PATIENTS WITH MULTIPLE RENAL TUMORS - B. Ya. Alekseev; A. S. Kalpinskiy; I. A. Taraki; A. A. Mukhomed’yarova; K. М. Nyushko; N. V. Vorobyev; A. A. Kostin; A. D. Kaprin (Исследования и практика в медицине)
Renal cell carcinoma (RCC) occupies one of the leading places in the world for morbidity among malignant neoplasms of the genitourinary system. The frequency of occurrence of bilateral RCC according to different authors is 2–6% of the total population of patients with RCC. Currently, the only effective method of treatment of bilateral RCC is surgical treatment. Patients with bilateral RCC are at high risk of dev eloping of local recurrence or progression of the disease after organ-preserving surgeries, which is why the surgeon is faced with a choice between a high risk of developing renal failure or relapse and/or progression of the disease, depending on the extent of the surgical intervention. According to the literature, in patients with bilateral RCC there was an increase in the incidence of papillary variant of RCC up to 19% and the presence of multifocal lesion. Surgical treatment of bilateral RCC is the only effective method to achieve satisfactory oncological results at a low incidence of complications. The m ost justified option for the treatment of bilateral RCC is the implementation of bilateral organ-preserving treatment, which allows achieving the optimal functional results. This article presents a clinical case of successful surgical treatment of a patient with bilateral RCC with multiple tumors.